Comparative and international policing, justice, and transnational crime - Kethineni, Sesha (Carolina Academic Press, 2021)
Justice systems in selected countries / Philip Reichel -- The role of international justice organizations / Donna Vandiver and J.D. Jamieson -- International law enforcement organizations / Mathieu Deflem and Shannon -- Policing in selected countries : organization and structure / Harry Dammer -- Policing subordinate sovereignties : policing in democratic societies / L. Edward Wells -- Correctional systems, philosophies, and innovations : a comparative perspective / Sesha Kethineni, Sarah McCullough and Tinu Neha Miriyam -- Juvenile justice : a comparative perspective / Sesha Kethineni, Sarah McCullough and Richard Charlton -- The global normative order : a call fo international individual rights in a world of states / Gabriel Rubin -- International human rights movement / Satenik Margaryan -- War crimes : international response to genocide / Ralph Weisheit -- Specific crimes against humanity : groups and minority rights / Sesha Kethineni, Colette B. Harris, and Gail Humiston -- International terrorism / JeffreyIan Ross and Michael Stohl -- Wildlife crime / Monique Sosnowski and William D. Moreto -- The war on migration and the crisis of nationalism / Gabriel Rubin and Ira Rosenberg -- International drug trafficking / Melanie-Angela Neuilly -- Human trafficking and policing in an international context / Gail Humiston and Roberto Hugh Potter -- International crimes : "Jus Cogens" and "Obligatio Erga Omnes" / Jessie L. Krienert, Jeffrey A. Walsh, Kevin Matthews, Meghan, and Peuterbaugh -- Cryptocurrency and crime / Sesha Kethineni and Dayanand Sundaravadivelu -- Overall conclusion.